ANALISIS TRANSFORMASI SOSIAL EKONOMI WILAYAH PERI URBAN DI KABUPATEN KAMPAR (Studi Kasus Desa Tarai Bangun Kecamatan Tambang) - Arfa Fadhilla; Rosyetti '; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in the village of Tarai Build Mining District of Kampar regency. The purpose of this study was to determine how the socio-economic transformation in peri urban area that occurred in the village of Tarai Bangun.The data used in this research is secondary data from the years 2006-2015 were obtained from the Village Office Tarai Bangun. To see the data used for social transformation total population by level of education and population density. Meanwhile, to see economic transformation used data on the number of population based jobs and facilities and infrastructures supporting economic activities of the population. The data analysis method used in this research is descriptive.The results showed that there has been a socio-economic transformation in Tarai Bangun Desa. The education level of the population was originally centered on complete primary school and junior high school or equivalent increased to graduate or equivalent and total undergraduate population also increased. With increasing population, the population density is also increased. Livelihood of the population also experienced a shift from the agricultural sector to the trade sector. The number of facilities and infrastructure in Tarai Bangun Desa also increased.Keywords: Tansformation, Social, Economic andPeri-Urban Area.